The impact of severe mental disorders and psychotropic medications on sexual health and its implications for clinical management. Issue 1 (19th January 2018) - Montejo, Angel L.; Montejo, Laura; Baldwin, David S.
Abstract : Sexual dysfunction often accompanies severe psychiatric illness and can be due to both the mental disorder itself and the use of psychotropic treatments. Many sexual symptoms resolve as the mental state improves, but treatment‐related sexual adverse events tend to persist over time, and are unfortunately under‐recognized by clinicians and scarcely investigated in clinical trials. Treatment‐emergent sexual dysfunction adversely affects quality of life and may contribute to reduce treatment adherence. There are important differences between the various compounds in the incidence of adverse sexual effects, associated with differences in mechanisms of action. Antidepressants with a predominantly serotonergic activity, antipsychotics likely to induce hyperprolactinaemia, and mood stabilizers with hormonal effects are often linked to moderate or severe sexual dysfunction, including decreased libido, delayed orgasm, anorgasmia, and sexual arousal difficulties. Severe mental disorders can interfere with sexual function and satisfaction, while patients wish to preserve a previously satisfactory sexual activity. In many patients, a lack of intimate relationships and chronic deterioration in mental and physical health can be accompanied by either a poor sexual life or a more frequent risky sexual behaviour than in the general population. Here we describe the influence of psychosis and antipsychotic medications, of depression and antidepressant drugs, and of bipolar disorder and mood stabilizers on sexual health, and the optimal management of patients with severe psychiatric illness and sexual dysfunction.